Strategi Komunikasi Edukasi Tuberkulosis Akun Instagram @tbc.komunitas berdasarkan The Circular Model of SOME Theory - Raisa Setya Rahmadhani; Sidiq Setyawan (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to examine how the Instagram account @tbc.komunitas, managed by PR Konsorsium Komunitas Penabulu-STPI, implements communication strategies in conducting health education and promotion, particularly regarding Tuberculosis, through the Circular Model of SOME Theory approach. This research employs a descriptive qualitative method with data collection techniques consisting of interviews with the communication team of PR Konsorsium Komunitas Penabulu-STPI and direct observation of the Instagram account @tbc.komunitas. The result show that the account utilizes social media as a medium for health education and promotion while applying communication strategies aligned with the stages of the Circular Model of SOME Theory. The share stage focuses on building identity and audience trust; optimize emphasizes content relevance to audience needs; manage involves interaction management and periodic evaluation; and engage is carried out through collaborations with the Ministry of Health and other health organizations. These strategies reflect the team’s efforts to establish adaptive and interactive communication in delivering health education, although the implementation has not yet been fully optimized.